2020
DOI: 10.1186/s12974-020-01736-1
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl fumarate alleviates the nitroglycerin (NTG)-induced migraine in mice

Abstract: Background: Oxidative stress and inflammatory pathways are involved in migraine and endogenous antioxidant defense system has a role in the prevention of hyperalgesia in migraine. In this study, we aimed to evaluate the role of the most pharmacologically effective molecules among the fumaric acid esters (FAEs), dimethyl fumarate, nuclear factor E2-related factor 2/antioxidant response element (Nrf-2/ARE) pathway-mediated, in regulating the hypersensitivity in a mouse model of nitroglycerine (NTG)-induced migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 73 publications
3
34
0
Order By: Relevance
“…Moreover, an in vitro study investigated the multiple mechanisms of DMF [ 10 ]; for the experiment, were used SH-SY5Y human neuroblastoma cell lines stimulated with amyloid-beta (Ab). The form of 42-amino acid of this peptide, Ab (1–42), has been shown to contribute to the pathogenesis of AD, and is also linked to oxidative stress and inflammation in the CNS [ 114 ].…”
Section: Dmf and Ndsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, an in vitro study investigated the multiple mechanisms of DMF [ 10 ]; for the experiment, were used SH-SY5Y human neuroblastoma cell lines stimulated with amyloid-beta (Ab). The form of 42-amino acid of this peptide, Ab (1–42), has been shown to contribute to the pathogenesis of AD, and is also linked to oxidative stress and inflammation in the CNS [ 114 ].…”
Section: Dmf and Ndsmentioning
confidence: 99%
“…In particular, Nrf2 has been proposed as a new pharmacological target in neuroinflammatory pathologies, including NDs [ 9 ]. Many papers highlighted the importance of molecules with antioxidant activities for the treatment of NDs, such as the fumaric acid esters (FAEs), where DMF represents the most pharmacologically effective molecule [ 10 ]. It has been shown that DMF acts as an Nrf2 activator, able to stimulate a cellular defense to protect neurons from ROS-induced damage [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Total cytosolic and nuclear extracts were prepared, as previously described [ 26 ], on saphene veins. The following primary antibodies were used: anti- IL-1β (Santa Cruz Biotechnology, Dallas, TX, USA, 1:500 #sc12742, D.B.A, Milan, Italy), anti-TNF-α (Santa Cruz Biotechnology; 1:500 #sc52746), anti-TGFβ1 (Santa Cruz Biotechnology, 1:500 #sc130348, D.B.A, Milan, Italy), anti-VEGF (Santa Cruz Biotechnology; 1:1000 #sc7269), anti- αSMA (Santa Cruz Biotechnology; 1:500 #sc53015) and anti-prolyl endopeptidase (Abcam; 1:1000,#ab58988) in 1× phosphate-buffer saline (Biogenerica srl, Catania, Italy), 5% w/v non-fat dried milk, 0.1% Tween-20 at 4 °C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…In a rat model of arthritis, a single intraperitoneal dose of MMF dose-dependently alleviated pressure hyperalgesia, as well as unevoked vocalizations, a sign of spontaneous pain [60]. In a nitroglycerine-induced migraine model, acute oral administration of DMF attenuated heat hyperalgesia and photophobia [61]. DMF also increased levels of NRF2, SOD2, and HO-1, while decreasing NFκB p65 levels in the whole brain [61].…”
Section: Chronic Painmentioning
confidence: 99%
“…In a nitroglycerine-induced migraine model, acute oral administration of DMF attenuated heat hyperalgesia and photophobia [61]. DMF also increased levels of NRF2, SOD2, and HO-1, while decreasing NFκB p65 levels in the whole brain [61]. However, the therapeutic mechanisms of action in both models remain to be defined.…”
Section: Chronic Painmentioning
confidence: 99%